Trend of suicide by self-immolation in a 13-year timeline: was the COVID-19 pandemic a potentially important stressor? - Jeremic, Jelena V.; Mihaljevic, Jovan M.; Radosavljevic, Ivan L. J.; Jurisic, Milana M.; Suđecki, Branko J.; Stojicic, Milan T.; Jovanović, Milan D.; Pavlovic, Zorana; Radenovic, Kristina G.; Milic, Nikola V.; Pavlovic, Vedrana; Milic, Natasa M.; et al. (Frontiers in Public Health, 2024)
Introduction: Self-immolation is an uncommon way of attempting and committing a suicide, with a fatality rate of 80%. The risk factors in self-immolation victims vary depending on demographic characteristics, socio-economic and cultural factors as well as religious beliefs. Whether the COVID-19 pandemic was a potentially important stressor for self-immolation is still unknown, with insufficient studies examining this issue. Therefore, in this study we aimed to examine the trend of self-immolation in a 13-year timeline, and the potential association of COVID-19 pandemic with the increase in the incidence and severity of self-immolation injuries in Serbia in 2021.The study included hospitalized patients due to intentional burns caused by self-immolation in the period from January 1, 2008 to December 31, 2021. Joinpoint regression analysis was used for the analysis of continuous linear trends of self-immolation cases with change points.Results: While a rising trend was observed in the 2008-2013 time segment, followed by a decline in the upcoming 2013-2016 time segment, a significant increase reached its maximum during COVID-19 pandemic (2021), with annual percent change of 37.1% (p=0.001). A significant increase in the median number of cases per year was observed during 2021 compared to the previous periods (7.5 vs 2). Frequency of patients with a psychiatric diagnosis versus those without a psychiatric diagnosis was significantly higher during than before the COVID-19 period (66.7% vs 36.1%, p=0.046). This is a provisional file, not the final typeset article Conclusion: In our study, a significant increase in the frequency of suicide attempts by self-immolation during COVID-19 pandemic was noticed. There was also an increased frequency of pre-existing psychiatric illness among patients during the pandemic period. With limited high-quality data available, the study adds to a rising body of evidence for assessment of outcomes of the pandemic on mental health and recognition of stressors for self-immolation.